Wrap film

JP2023128982A5Active Publication Date: 2025-03-13KUREHA CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022033697
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-03-13
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Existing wrap films made of polyvinylidene chloride resin face challenges in maintaining excellent barrier properties while reducing the use of chemical additives, often leading to appearance defects such as white spots.

Method used

A wrap film composed of a vinylidene chloride-vinyl chloride copolymer with specific additive contents of diacetylated monoglyceride and epoxidized soybean oil, within a defined mass percentage range, and a thickness of 5 to 15 μm, is developed to address these issues.

Benefits of technology

The film achieves excellent barrier properties with no appearance defects, such as white spots, and maintains desirable mechanical properties like Young's modulus, while reducing the use of additives.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a wrap film having excellent barrier properties without external appearance defects such as white spots.SOLUTION: In this wrap film, made from a resin composition containing a vinylidene chloride-vinyl chloride copolymer, the resin composition contains diacetylated monoglyceride and epoxidized soybean oil as additives, the content of the additives in the resin composition is 4.5-6.0 mass%, the content of the diacetylated monoglyceride in the resin composition is 0.9-3.5 mass%, and the thickness of the wrap film is 5-15 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a wrap film made of a resin composition containing a vinylidene chloride-vinyl chloride copolymer. [Background technology]

[0002] Films made of polyvinylidene chloride resins (hereinafter abbreviated as "PVDC resins"), which are polymers of monomers containing vinylidene chloride, are widely used as wrap films for household or industrial use because of their excellent properties such as adhesion to containers, transparency, barrier properties, heat resistance, aroma retention, and firmness and resilience. Such wrap films are disclosed, for example, in Patent Document 1.

[0003] In order to achieve a balanced expression of the various excellent properties described above in wrap films, various additives such as plasticizers and stabilizers are often blended into the PVDC resin (see paragraph 0020 of Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2011-168750 Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, there is a demand from consumers for a reduction in the amount of chemical substances used as additives in a variety of products, not just wrap films. However, simply reducing the amount of additives used in the wrap film will deteriorate various properties of the wrap film, making it difficult to provide a wrap film that is free of appearance defects such as white spots and has excellent barrier properties.

[0006] The present invention has been made in view of the above problems, and its object is to provide a wrap film that is free from appearance defects such as white spots and has excellent barrier properties. [Means for solving the problem]

[0007] The present inventors have discovered that the above problems can be solved by adding diacetylated monoglyceride and epoxidized soybean oil as additives to a wrap film made from a resin composition containing vinylidene chloride-vinyl chloride copolymer, setting the content of the additives in the resin composition to 4.5 to 6.0 mass%, the content of diacetylated monoglyceride in the resin composition to 0.9 to 3.5 mass%, and setting the thickness of the wrap film to 5 to 15 μm, thereby completing the present invention.

[0008] That is, the present invention is A wrap film made of a resin composition containing vinylidene chloride-vinyl chloride copolymer, The resin composition contains diacetylated monoglyceride and epoxidized soybean oil as additives, The content of the additive in the resin composition is 4.5 to 6.0 mass %, The content of diacetylated monoglyceride in the resin composition is 0.9 to 3.5% by mass, Provided is a wrap film having a thickness of 5 to 15 μm. [Effects of the Invention]

[0009] According to the present invention, it is possible to provide a wrap film that is free from appearance defects such as white spots and has excellent barrier properties. DETAILED DESCRIPTION OF THE INVENTION

[0010] <Wrapping film> The wrap film is made of a resin composition containing vinylidene chloride-vinyl chloride copolymer, and the resin composition contains diacetylated monoglyceride and epoxidized soybean oil as additives. The content of the additive in the resin composition is 4.5 to 6.0 mass %, and more preferably 5.0 to 6.0 mass %. The content of diacetylated monoglyceride in the resin composition is 0.9 to 3.5 mass %, more preferably 2.2 to 3.5 mass %. The thickness of the wrap film is 5 to 15 μm. The wrap film is free from appearance defects such as white spots and has excellent barrier properties.

[0011] The wrap film has excellent barrier properties. Specifically, the wrap film has an oxygen permeability of 25 to 40 cm per 10 μm of thickness measured at 20° C. 3 / (m 2 ·day·atm) is preferable, and 30 to 38 cm 3 / (m 2 ·day·atm) is more preferable. In addition, the water vapor permeability of the wrap film measured at 40°C and 90% RH per 10 μm of thickness is 5 to 15 cm 3 / (m 2 ·day·atm) is preferable, and 6 to 13 cm 3 / (m 2 ·day·atm) is preferred.

[0012] Furthermore, the wrap film exhibits a good Young's modulus. Specifically, the Young's modulus in the MD (machine direction), measured in accordance with JIS-K7127, is preferably 430 to 520 MPa, and more preferably 439 to 514 MPa. The Young's modulus in the TD (transverse) direction, measured in accordance with JIS-K7127, is preferably 350 to 430 MPa, and more preferably 354 to 423 MPa.

[0013] <Resin composition> As described above, the wrap film is made of a resin composition containing vinylidene chloride-vinyl chloride copolymer and additives.

[0014] The acetone extractable amount of the resin composition is preferably 10 to 13 mass % The acetone extractable amount is measured by the method described later in the examples. The amount of acetone extractables can be measured by the method described later in the Examples. When the amount of acetone extractable is within the above range, white spots do not occur even if the amount of additives is reduced, and a film can be obtained without any problems in processability.

[0015] The vinylidene chloride-vinyl chloride copolymer and additives will be described below.

[0016] [Vinylidene chloride-vinyl chloride copolymer] A vinylidene chloride-vinyl chloride copolymer (hereinafter also simply referred to as a "copolymer") contains vinylidene chloride units, which are structural units derived from vinylidene chloride, and vinyl chloride units, which are structural units derived from vinyl chloride. The copolymer is preferably produced by suspension polymerization or emulsion polymerization of 60 to 98 mass % vinylidene chloride and 2 to 40 mass % vinyl chloride, more preferably 70 to 95 mass % vinylidene chloride and 5 to 30 mass % vinyl chloride, and even more preferably 87 to 91 mass % vinylidene chloride and 9 to 13 mass % vinyl chloride. That is, in the copolymer, the vinylidene chloride content in the vinylidene chloride-vinyl chloride copolymer, which is the ratio of the mass of vinylidene chloride units to the sum of the mass of vinylidene chloride units and the mass of vinyl chloride units, is preferably 60 to 98 mass%, more preferably 70 to 95 mass%, and even more preferably 87 mass% or more and 91 mass% or less. When vinylidene chloride and vinyl chloride are copolymerized in the above ratio, there tends to be a good balance between extrusion processability during film formation and the gas barrier properties of the resulting film.

[0017] In the copolymer, the molar fraction of the diadjunct moiety (VD-VC moiety) consisting of one vinylidene chloride unit and one vinyl chloride unit in succession is preferably 25.3 mol% to 26.7 mol%, more preferably 25.6 mol% to 26.5 mol%, based on the total structural units. When the molar fraction is within the above range, the adhesion of the resulting film is likely to be improved. In this specification, the molar fraction of the diadjunct moiety refers to a value calculated based on the results of NMR measurement of the film, as described in detail in the Examples.

[0018] In the copolymer, the molar fraction of diaduplicate moieties (VC-VC moieties) consisting of two consecutive vinyl chloride units is preferably 3.5 mol % to 5.0 mol %, more preferably 3.7 mol % to 4.5 mol %, based on the total structural units. When the molar fraction is within the above range, the adhesion of the resulting film is likely to be further improved.

[0019] The weight-average molecular weight of the copolymer is preferably 85,000 to 100,000, more preferably 90,000 to 100,000, and even more preferably 90,000 to 95,000. In this specification, the molecular weight refers to the molecular weight in terms of polystyrene measured by gel permeation chromatography. When the weight-average molecular weight is within this range, extrusion processability and film-forming properties tend to be excellent even when the amount of additives is reduced.

[0020] [Additives] The resin composition contains the copolymer and an additive. The resin composition essentially contains diacetylated monoglyceride (hereinafter also referred to as DALG) and epoxidized soybean oil (hereinafter also referred to as ESBO) as additives. In terms of processability, the resin composition preferably contains acetyl tributyl citrate (hereinafter also referred to as ATBC) in addition to DALG. ATBC and DALG are plasticizers. ESBO is a stabilizer.

[0021] The content of the additive in the resin composition is 4.5 to 6.0 mass %, and more preferably 5.0 to 6.0 mass %. The content of DALG in the resin composition is 0.9 to 3.5 mass %, preferably 1.8 to 3.5 mass %, and more preferably 2.2 to 3.5 mass %. When the resin composition contains a DALG within the above range, the vinylidene chloride-vinyl chloride copolymer is well plasticized, and a wrap film exhibiting a desirable dynamic friction coefficient is easily obtained. When the resin composition contains ATBC, the content of ATBC in the resin composition is preferably 0.3 to 3.6 mass %, more preferably 0.3 to 2.7 mass %, and even more preferably 0.4 to 2.3 mass %. By forming a resin composition containing additives and DALG in amounts within these ranges into a film having a thickness of 5 to 15 μm, a wrap film with excellent barrier properties and no appearance defects such as white spots can be obtained.

[0022] In the specification and claims of the present application, the content of component X in a resin composition being Y mass % means that the ratio of the mass of component X to the mass of the entire resin composition is Y mass %.

[0023] The resin composition may contain additives other than DALG and ESBO, as long as the above-mentioned requirements are met. The additives may be organic or inorganic. Examples of other additives include plasticizers other than DALG, stabilizers other than ESBO, surfactants, lubricants, etc. The other additives may be used alone or in combination of two or more. The content of additives other than ATBC, DALG, and ESBO in the resin composition is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass.

[0024] When the resin composition contains ATBC, the total content of ATBC and DALG in the resin composition is preferably 2.5 to 4.5 mass%, more preferably 2.7 to 4.0 mass%, in order to easily obtain a wrap film with excellent barrier properties. When the resin composition contains ATBC, the total content of ATBC and ESBO in the resin composition is preferably 2.4 to 4.0 mass%, more preferably 2.4 to 3.5 mass%, in order to easily obtain a wrap film with excellent barrier properties. In order to easily obtain a wrap film with excellent barrier properties, the total content of DALG and ESBO in the resin composition is preferably 1.9 to 6.0 mass%, more preferably 3.4 to 6.0 mass%, even more preferably 5.0 to 5.5 mass%, and particularly preferably 5.2 to 5.5 mass%. In order to easily obtain a wrap film with excellent barrier properties, the total content of DALG and ESBO relative to the mass of the additives contained in the resin composition is preferably 31.7% by mass to 100% by mass, more preferably 56.7% by mass to 100% by mass, even more preferably 83.3% by mass to 100% by mass, and particularly preferably 86.7% by mass to 100% by mass.

[0025] (plasticizer) DALG is essential as a plasticizer. As mentioned above, the resin composition preferably contains ATBC as a plasticizer together with DALG. As the DALG, for example, diacetyl monolauryl glyceride is used. Other examples of plasticizers as additives include dioctyl phthalate, acetyl tributyl citrate, dibutyl sebacate, dioctyl sebacate, acetylated diglyceride, acetylated triglyceride, etc. The plasticizers may be used alone or in combination of two or more. In order to prevent the occurrence of white spots on the wrap film, the content of other plasticizers, particularly dibutyl sebacate and dioctyl sebacate, in the resin composition is preferably 0.5% by mass or less, more preferably 0.1% by mass or less, and particularly preferably 0% by mass.

[0026] (stabilizer) ESBO is essential as a stabilizer. Examples of other stabilizers as additives include epoxidized vegetable oils other than ESBO, such as epoxidized linseed oil, amide derivatives of alkyl esters, magnesium hydroxide, tetrasodium pyrophosphate, etc. The stabilizers may be used alone or in combination of two or more. In order to easily obtain a wrap film with excellent barrier properties, the content of ESBO in the resin composition is preferably 1 to 3 mass %, more preferably 1.6 to 2.9 mass %, and most preferably 2.0 to 2.8 mass %.

[0027] (surfactant) Examples of surfactants include nonionic surfactants such as glycerin fatty acid esters, polyglycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc. The surfactants may be used alone or in combination of two or more.

[0028] (lubricant) Examples of lubricants include inorganic lubricants such as silicon dioxide, zeolite, and calcium carbonate; and organic lubricants such as saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, and thioether compounds. The lubricants may be used alone or in combination of two or more.

[0029] Examples of saturated fatty acid amides include butylamide, valeramide, caproamide, caprylic acid amide, capric acid amide, lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, arachidic acid amide, and behenic acid amide. Examples of unsaturated fatty acid amides include oleic acid amide and erucic acid amide. Examples of substituted amides include N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, and N-stearyl erucic acid amide. Examples of thioether compounds include dilauryl thiodipropionate, ditridecyl thiodipropionate, dimyristyl thiodipropionate, distearyl thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), pentaerythritol tetrakis(3-dodecylthiopropionate), pentaerythritol tetrakis(3-octadecylthiopropionate), pentaerythritol tetrakis(3-myristylthiopropionate), and pentaerythritol tetrakis(3-stearylthiopropionate).

[0030] <Wrapping film manufacturing method> The method for producing a wrap film typically includes a polymerization step of polymerizing vinylidene chloride and vinyl chloride to obtain a vinylidene chloride-vinyl chloride copolymer, and a molding step of molding the copolymer.

[0031] In the polymerization step, examples of the polymerization method include suspension polymerization and emulsion polymerization, which are heterogeneous polymerization methods, and suspension polymerization is preferred in terms of workability, productivity, resource conservation, purity of the vinylidene chloride-vinyl chloride copolymer, etc. Polymerization conditions such as polymerization temperature and polymerization time are appropriately selected according to well-known polymerization conditions so as to obtain a copolymer having desired physical properties and a desired molecular weight.

[0032] In the molding step, examples of the molding method include melt extrusion, solution casting, and calendaring, with melt extrusion being preferred in terms of workability, productivity, resource conservation, resin film properties, etc. Examples of melt extrusion methods include the T-die method and inflation method, with inflation method being preferred. The inflation method requires simple equipment and can produce wide films from a small mold.

[0033] <Wrapping film> The wrap film according to the present invention is made of the resin film according to the present invention, and has excellent adhesion, just like the resin film. [Example]

[0034] The present invention will be explained in more detail below by showing examples, but the scope of the present invention is not limited to these examples.

[0035] [Examples 1 to 3, Comparative Examples 1 and 2] Vinylidene chloride (VD) and vinyl chloride (VC) were mixed in the ratio (VD / VC) shown in Table 1 and subjected to suspension polymerization to obtain a copolymer. The additives ATBC, DALG, ESBO, and dibutyl sebacate (DBS) were added to the obtained copolymer so that the respective contents in the resin composition were as shown in Table 1, and mixed to produce a compound. The compound was then annularly melt-extruded using a single-screw extruder at a resin temperature of approximately 185°C, quenched in a 10°C cooling bath, and then subjected to biaxial inflation stretching at room temperature and slit to obtain a film with the thickness shown in Table 1. The same copolymer was used in Examples 1 to 3. The same copolymer was used in Comparative Examples 1 and 2.

[0036] The ratio of the diadduct moieties in the resulting copolymer was measured according to the following method. The measurement results are shown in Table 1.

[0037] <Ratio measurement of bipartite region> For the films produced, the proportions of diadult moieties consisting of two consecutive vinyl chloride units (VD-VD moieties), diadult moieties consisting of one consecutive vinylidene chloride unit and one consecutive vinyl chloride unit (VD-VC moieties), and diadult moieties consisting of two consecutive vinyl chloride units (VC-VC moieties) were calculated as molar fractions based on the results of NMR measurements.

[0038] 1 g of film was collected, 50 ml of THF was added, and the mixture was dissolved at 50°C. 300 ml of methanol was then slowly added to cause reprecipitation. The reprecipitate was filtered, dried, and purified. 35 mg of the purified reprecipitate was collected and placed in a test tube, and 0.75 ml of deuterated THF (measurement solvent) was added to dissolve it uniformly. 0.35 ml of the solution was sampled and subjected to NMR measurement using a high-resolution proton nuclear magnetic resonance spectrometer (JEOL RESONANCE, Inc., FT-NMR JNM-EX270). Measurements were performed at 5-second intervals and 128 accumulations, and a spectrum was obtained with the horizontal axis representing the chemical shift relative to the tetramethylsilane signal.

[0039] Hereinafter, the vinylidene chloride unit (-CH2-CCl2-) is represented as A, and the vinyl chloride unit (-CH2-CHCl-) is represented as B, and the signals 1, 2, and 3 obtained on the spectrum are assigned as follows: Signal 1 (approximately 5.2 to 4.5 ppm) was assigned to the CH signal of B (methine (CH) group of the structural unit derived from vinyl chloride). Signal 2 (approximately 4.2 to 3.8 ppm) was assigned to the CH2 signal of one of the A's in AA (the methylene (CH2) group of the structural unit derived from vinylidene chloride). Signal 3 (approximately 3.5-2.8 ppm) was assigned to the CH2 signal of A in both AB and BA (methylene (CH2) group of the structural unit derived from vinylidene chloride).

[0040] The molar fraction of the structural unit or dyad moiety was calculated from the spectral area values ​​of these signals (areas of the signals in the NMR spectrum). Each molar fraction is expressed as follows: Mole fraction of A (mol%): P(A) Molar fraction of B (mol%): P(B) Molar fraction (mol%) of AA (a diadduct consisting of two consecutive vinylidene chloride units): P(AA) Molar fraction (mol%) of AB (a diadduct consisting of one vinylidene chloride unit and one vinyl chloride unit) : P(AB) Molar fraction (mol%) of BB (a diadduct consisting of two consecutive vinyl chloride units): P(BB)

[0041] From the area values ​​(areas of peaks in the NMR spectrum) of signals 1, 2, and 3 assigned as above, the integral values ​​of the signals on the spectrum were assigned as follows: The integral value of signal 1 (approximately 5.2 to 4.5 ppm) is calculated as B 1 For 1 H The integral value of signal 2 (approximately 4.2 to 3.8 ppm) is 1 H2 pieces The integral value of signal 3 (approximately 3.5 to 2.8 ppm) is 1 4 H

[0042] Each mole fraction was calculated using the following formula: P(A) + P(B) = 100 ·P(AA) + P(BB) + P(AB) + P(BA) = 100 P(AB) = P(BA) P(A) = P(AA) + P(AB) P(B) = P(BB) + P(BA)

[0043] P(A) and P(B) are calculated using the following equation (Equation 3). (Number 3) P(B):P(A) = Signal 1 integral:(Signal 2 integral + Signal 3 integral / 2) / 2 P(A)=100-P(B)

[0044] P(AA) and P(BB) are calculated using (Equation 4) and (Equation 5). (Number 4) P(AA):P(AB) = Signal 2 integral: Signal 3 integral / 2 P(AB)=P(A)-P(AA) (Number 5) P(BB) = 100 - P(AA) - P(AB) - P(BA)

[0045] The resin compositions obtained by the above method were subjected to measurement of the methanol extractable amount and the acetone extractable amount according to the following methods. The obtained film was visually inspected for the presence or absence of white spots, and the Young's modulus, dynamic friction coefficient, oxygen permeability, and water vapor permeability were measured according to the following methods. The evaluation and measurement results are shown in Table 1.

[0046] <Method for measuring the amount of methanol extracted> 10 g of the resin composition (compound) was placed in a cylindrical filter paper and extracted with approximately 120 mL of methanol at 90°C for 24 hours using a Soxhlet extractor. After extraction, the methanol was dried at 90°C, and the residue was dried at 105°C for 1 hour. After drying, the flask containing the extract was allowed to cool in a desiccator, and the mass of the flask containing the extract was determined. The amount of methanol extracted was calculated using the following formula. Methanol extractable amount [%] = (BA) / C × 100 A: Mass of the flask containing the extract (g) B: Mass of the flask (g) C: mass of the sample (g) (C = 10 g)

[0047] <Method for measuring acetone extractables> After methanol extraction using the above method, 5 g of the sample was placed in an Erlenmeyer flask, 150 mL of acetone was added, and the sample was stirred in acetone for 5 hours at 50 °C with a reflux condenser attached. A 100 mL aliquot was taken from the resulting extract and filtered through filter paper No. 5A (compliant with JIS P 3801-1995, "Filter Paper (for Chemical Analysis)"). The resulting filtrate was placed in a 150 mL flat-bottom flask that had been previously dried and weighed. The filtration equipment used was washed with carbon tetrachloride, and the washings were added to the flat-bottom flask. The acetone contained in the filtrate was then dried in a thermostatic water bath regulated at 80 °C. The flat-bottom flask containing the extract was then dried for 1 hour in a dryer regulated at 105 °C. The dried flat-bottom flask was then allowed to cool in a desiccator for 1 hour, and the mass of the flask containing the extract was determined. The amount of acetone extracted was calculated using the following formula: Acetone extractables % = {(AB) x E / (C x D)} x 100% A: Mass of the flat-bottom flask containing the extract (g) B: Mass of the flat-bottom flask (g) C: mass of the sample (g) (C = 5g) D: Amount of extracted liquid collected (mL) E: Amount of acetone used for extraction (mL) (E = 150 mL)

[0048] <Method for measuring Young's modulus> According to JIS-K7127, a measurement sample was obtained by cutting a film into a length of 200 mm and a width of 20 mm in a direction parallel to the MD direction and a direction parallel to the TD direction of the film. Measurements were carried out in an atmosphere of 23°C and 50% RH. Using an A&D TENSILON RTC-1210A, the wrap film was set with a chuck distance of 10 cm and pulled up and down at a rate of 10 mm / min. The strength at the point of 2.5% displacement (stroke 2.5 mm) was multiplied by 40 and converted to 100% displacement to obtain the Young's modulus (unit: MPa).

[0049] <Method for measuring the coefficient of dynamic friction> Using a static and dynamic friction measuring instrument (Type: TL201Ts) manufactured by Trinity Lab Co., Ltd., a tactile contact was used. A vertical load of 20 g was applied to the tactile contact, and with the film sample fixed to the stage, the tactile contact was moved in the MD of the film at a speed of 3.3 mm / min to measure the dynamic friction coefficient.

[0050] <Method for measuring oxygen permeability> The oxygen permeability was measured using the OX-TRAN 2 / 21 model manufactured by MOCON in accordance with ASTM D3985-81 (unit: cm 3 / m 2 The values ​​per unit thickness (10 μm) are shown in Table 1. Measurements were carried out under dry conditions at 20°C.

[0051] <Method for measuring water vapor permeability> The water vapor permeability was measured using a MOCON PERMATRAN-W (registered trademark) 3 / 33 model in accordance with JIS K7129-1992 (unit: g / m 2 ·day), and the values ​​per unit thickness (10 μm) are shown in Table 1. The measurements were carried out under conditions of 40°C and 90% RH.

[0052] [Table 1]

[0053] According to Table 1, a wrap film consisting of a resin composition containing vinylidene chloride-vinyl chloride copolymer and, as additives, diacetylated monoglyceride and epoxidized soybean oil, in which the content of the additive in the resin composition is 4.5 to 6.0 mass%, the content of the diacetylated monoglyceride in the resin composition is 0.9 to 3.5 mass%, and the thickness is 5 to 15 μm, is free from appearance defects such as white spots and has excellent barrier properties.

Claims

1. A wrap film made of a resin composition containing a vinylidene chloride-vinyl chloride copolymer, The resin composition contains diacetylated monoglyceride and epoxidized soybean oil as additives, The content of the additive in the resin composition is 5.0 to 6.0% by mass, The content of the diacetylated monoglyceride in the resin composition is 0.9 to 3.5% by mass, The content of the diacetylated monoglyceride and the epoxidized soybean oil in the resin composition is 5.0 to 5.5% by mass, A wrap film having a thickness of 5 to 15 μm.

2. The wrap film according to claim 1, wherein the content of the epoxidized soybean oil in the resin composition is 1.9 to 3.0% by mass.

3. A wrap film as described in claim 1 or 2, wherein the sum of the content of the diacetylated monoglyceride and the content of the epoxidized soybean oil relative to the mass of the additive is 83.3 to 100 mass%.

4. Oxygen permeability per 10 μm thickness measured at 20°C is 25 to 40 cm 3 / (m 2 ・day・atm) The Young's modulus in the MD (machine direction) measured in accordance with JIS-K7127 is 430 to 520 MPa; The wrap film according to any one of claims 1 to 3, having a Young's modulus in the TD (transverse) direction of 350 to 430 MPa, measured according to JIS-K7127.

5. The wrap film according to any one of claims 1 to 4, wherein the vinylidene chloride content in the vinylidene chloride-vinyl chloride copolymer, which is the ratio of the mass of vinylidene chloride units to the sum of the mass of vinylidene chloride units and the mass of vinyl chloride units, is 87% by mass or more and 91% by mass or less.

6. The wrap film according to any one of claims 1 to 5, wherein the weight average molecular weight of the vinylidene chloride-vinyl chloride copolymer is 85,000 to 100,000.